2019
DOI: 10.1108/sjme-06-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Facebook’s power: factors influencing followers’ visit intentions

Abstract: Purpose The purpose of this paper is to examine the role that Facebook Fan Pages (FFPs) play in the generation of visit intention. The study has three objectives: first, to examine the effects of museum-generated content (MGC) on perceived information quality and perceived customer service and perceived information quality and perceived customer service on visit intention and, second, to test the model with two samples to make comparisons that provide useful insights. Design/methodology/approach Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 104 publications
1
6
0
1
Order By: Relevance
“…PLS-SEM is a structural equation modeling technique based on variance (Hair et al, 2012); it is a useful tool for theorizing in management research in general (Hair et al, 2018). The use of PLS-SEM in the present study is supported by the research objectives, the non-normal distribution of some indicators and the sample size (Hair et al, 2012(Hair et al, , 2014Blasco-Lopez et al, 2019;Chien and Chi, 2019). In addition, using this nonparametric method technique is very appropriate, first, because it allows us to simultaneously analyze all the inter-variable relationships, including measurement and structural components, in a conceptual model (Henseler et al, 2016) and, second, it is highly suitable for MGAs (Hair et al, 2014;Henseler et al, 2016;Sarstedt et al, 2011).…”
Section: Reliability and Validity Of The Scalesmentioning
confidence: 87%
“…PLS-SEM is a structural equation modeling technique based on variance (Hair et al, 2012); it is a useful tool for theorizing in management research in general (Hair et al, 2018). The use of PLS-SEM in the present study is supported by the research objectives, the non-normal distribution of some indicators and the sample size (Hair et al, 2012(Hair et al, , 2014Blasco-Lopez et al, 2019;Chien and Chi, 2019). In addition, using this nonparametric method technique is very appropriate, first, because it allows us to simultaneously analyze all the inter-variable relationships, including measurement and structural components, in a conceptual model (Henseler et al, 2016) and, second, it is highly suitable for MGAs (Hair et al, 2014;Henseler et al, 2016;Sarstedt et al, 2011).…”
Section: Reliability and Validity Of The Scalesmentioning
confidence: 87%
“…Some authors have previously confirmed the relationship between HGC messages and perceived quality of information in the context of web design (Eroglu et al, 2003) and museum context (Blasco-Lopez et al, 2019). Applying this type of relationship to the hotel sector, the following hypothesis is proposed: H1.…”
Section: Theoretical Backgroundmentioning
confidence: 88%
“…A website with quality content provides new, accurate, organized and well-presented information that helps a company improve users' behavioral intentions (Le et al, 2020). In the same way, the effect of the perceived quality of information on social media influences purchase or visit intentions (Blasco-Lopez et al, 2019;Fu et al, 2020). Consequently, the following hypothesis is proposed: H4.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Instagram is regarded as the natural platform for developing marketing actions with influencers, so nearly nine out of ten marketers prefer to use it in their influencer marketing campaigns (Relatabe, 2019). Influencers are, in essence, present-day opinion leaders (Casal o et al, 2018) and, like all opinion leaders, they exert unequal influence on the decision-making processes of others (Rogers and Cartano, 1962;Blasco-L opez et al, 2019). They are considered as role models by other users, who follow their advice because they trust their beliefs and opinions (Casal o et al, 2018).…”
Section: Introductionmentioning
confidence: 99%